PENGARUH TEKNIK POE TERHADAP KETERAMPILAN PROSES SAINS SISWA KELAS IV SEKOLAH DASAR - Santi, Klara; Kresnadi, Hery; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the effect of implementation predict observe explain technique on natural science learning to science process skills of 4th grade students of Pontianak Kota 66 Public Elemantary School. This research use experimental method, research form pre-experimental design with one group pretest-posttest design type. The sampling technique use purposive sampling type totaling 30 students. Data collection techniques use direct observation and measurement techniques. The research instrument used was a objective test with multiple choice form. Based on data analysis result, average pre-test and post-test score were 67,83 and 74,57. Result of t-test obtained tcount = 5,18 and ttable =2,031 (Î± = 5%; db = 29). Because tcount (5,18) > ttable (2,031), its mean Ha accepted and H0 rejected. The effect size result is 0,72 with high criteria. The conclusion in this study is that there is the effect of implementation predict observe explain technique on natural science learning to science process skills of 4th grade students of Pontianak Kota 66 Public Elemantary School with high criteria.Â Keyword : The Effect, Predict Observe Explain Technique, Science Process Skills, Natural Science Learning